DIPG-53. Long-term survival from a Phase 1 dose-escalation trial using convection-enhanced delivery (CED) of radioimmunotherapeutic124I-omburtamab for treatment of diffuse intrinsic pontine glioma (DIPG). (3rd June 2022) - Souweidane, Mark M; Kramer, Kim; Pandit-Tasker, Neeta; Haque, Sofia; Zanzonico, Pat; Carrasquillo, Jorge; Lyashchenko, Serge K; Thakur, Sunitha B; Khakoo, Yasmin; Dunkel, Ira J; Donzelli, Maria; Lewis, Jason S; et al.
Abstract: BACKGROUND: Median survival from DIPG is less than one year. In a phase 1 dose escalation study (clinicaltrials.gov NCT01502917) 124 I-omburtamab targeting B7-H3 was administered intratumorally using CED. METHODS: CED was performed between 4-14 weeks post radiation therapy. Using a 3 + 3 design, 124 I-omburtamab was escalated from 0.25-10.0 mCi and infusion volumes (Vi) from 250-10, 000 µl with serial 124 I PET/CT performed up to ~1 week post-administration. Toxicities were assessed for 30 days. Dose escalation safety was evaluated. Survival was calculated using Kaplan-Meier statistics. RESULTS: 46 children were treated and evaluable for toxicity and survival;4 patients received partial doses and were evaluable for toxicity only. Three patients experienced dose limiting toxicities. Eleven patients had transient treatment related grade 3 toxicities with no grade 4 or 5 toxicities. Grade 3 nervous system toxicities included: muscular weakness(n=8), dysarthria(n=4), ataxia(n=3), dysphagia(n=3), and gait disturbance(n=1). Lesion absorbed doses ranged from 1, 000-1, 500cGy/mCi, with lesion-to-whole body radiation absorbed-dose ratios of ~900. A dose of 8mCi and infusion volume of 8, 000 µl is safe and may provide a distribution volume up to 20cm 3 . Median survival was 15.3 months (n =46, 95% CI 12.7, 17.3). Survival rate estimates (95% CI) at 1, 2, 3 and 5 years were 0.67 (0.55;0.82); 0.18 (0.09;0.35); 0.10 (0.04;0.26); and 0.05 (0.01;0.20). Four patients survived >3 years; two remain alive (61+ and 106+ months);two have died (44 and 53 month) with distant CNS disease and one with extra-CNS metastasis. CONCLUSION: Administration of escalating doses and volumes of 124 I-omburtamab via CED was a viable option for this patient subgroup. The median overall survival was increased 3-4 months compared to historical controls. Anecdotal long-term survival if validated with a planned phase 2 trial would support the concept of whole neuroaxis treatment in combination with CED in a subset of DIPG patients.